SOWING-DATE ON STUDIES ON MAIZE (ZEA MAYS L.) UNDER RAINFOREST CONDITIONS: EFFECT OF SOWING DATE ON GRAIN YIELD AND YIELD COMPONENTS. - Abasi , S. A. A.; Aofolajuwonlo, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study was conducted to determine the influence of sowing date in the tropical rainforest location of the study on grain yield and yield components of maize (Zea mays L.) Two maize cultivars, FARZ 7 and FARZ 34 were sown on five dates over a two-year period, 1983 and 1984. Sowing date had a highly significant effect on grain yield components, number of grains was most highly related to yield. It accounted for 83.3% of the variation in yield. It was followed by ear number and kernel weight which had coefficients of dates. It also had the greatest influence on grain number, ear length and kernel weight.